HUBUNGAN PELAYANAN INFORMASI OBAT TERHADAP KEPATUHAN MINUM OBAT PASIEN HIPERTENSI DI RSUD PENAJAM PASER UTARA - Triswanto Sentat (Jurnal Ilmiah Manuntung, 2017)
The Drug Information Service or Pelayanan Informasi Obat (PIO) is indispensable for improving patient compliance with their treatment. With the PIO can change the knowledge and compliance of patients, especially hypertensive patients. This study was conducted to determine whether PIO can influence adherence to medication hypertension patients in RSUD Penajam Paser Utara. Sampling was done by purposive sampling and analyzed using Spearman Rank Correlation Test where the compliance aspect was assessed using validity and reliability tested questionnaire method, given before PIO and after PIO, and Pill Count method (calculating the remaining pills for 4 weeks) . Samples were obtained by 50 people, the results showed no improvement in adherence before and after PIO administration, and there was a relationship of compliance measurement results with questionnaire method after counseling and Pill Count method. The percentage of patient adherence after PIO administration was based on a high-compliance 70% (35 person) questionnaire method and based on the Pill Count method with a high adherence rate of 60% (30 persons), the compliance data obtained from both methods indicated that the provision of PIO can not improve compliance to take medication of hypertension patient of RSUD Penajam Paser Utara